Candida auris: What Have We Learned About Its Mechanisms of Pathogenicity? - Rossato, Luana; Colombo, Arnaldo Lopes (Frontiers in Microbiology, 2018)
Candida auris has emerged globally as a multidrug-resistant (MDR) medical care-associated fungal pathogen. Recent reports have demonstrated that C. auris usually expresses fewer virulence factors than does Candida albicans. However, the tendency of C. auris transmission within and between healthcare facilities is unique among Candida spp. and is possibly promoted by virulence and pathogenicity factors that facilitate skin colonization and environmental persistence. To understand the ability of this yeast to cause disease, we herein discuss several virulence and pathogenicity aspects of C. auris.